Social Capital and The Power of Relationship: Social Capital and The Power of Relationship - Mohd Mahzan Bin Awang (Social Studies Education Department, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, 2022)
Social Capital and The Power of Relationship presented by MOHD MAHZAN BIN AWANG